THE EFFECT OF LEVERAGE, PRODUCTIVITY, AND DEVIDEND POLICY ON COMPANY VALUE WITH COMPANY SIZE AS A MODERATOR IN MANUFACTURING COMPANIES IN THE CONSUMER GOODS INDUSTRY SECTOR LISTED ON THE IINDONESIA STOCK EXCHANGE - Willman S; Fahmi Natigor Nasution; Isfenti Sadalia (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the effect of leverage, productivity, and dividend policy on firm value in consumer goods industry sector companies listed on the Indonesia Stock Exchange during the period 2022-2024, and to examine the role of firm size as a moderating variable. The research sample was determined using purposive sampling, resulting in 24 companies with 72 panel data observations. The analytical method used is Moderated Regression Analysis (MRA) with a Fixed Effect Model (FEM-EGLS) approach selected through Chow and Hausman tests. Results show that leverage has a positive and significant effect on firm value, while productivity has a positive but insignificant effect, and dividend policy has a negative but insignificant effect on firm value. Firm size significantly moderates the effect of leverage on firm value in a negative direction (pure moderator), but is unable to moderate the effects of productivity and dividend policy on firm value. These findings imply that capital structure management must be optimized, while asset utilization efficiency and dividend policy require more effective management to provide positive signals to investors.